2017
DOI: 10.1111/mec.14034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular response of Sargassum vulgare to acidification at volcanic CO2 vents: insights from de novo transcriptomic analysis

Abstract: Ocean acidification is an emerging problem that is expected to impact ocean species to varying degrees. Currently, little is known about its effect on molecular mechanisms induced in fleshy macroalgae. To elucidate genome wide responses to acidification, a transcriptome analysis was carried out on Sargassum vulgare populations growing under acidified conditions at volcanic CO vents and compared with populations in a control site. Several transcripts involved in a wide range of cellular and metabolic processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 81 publications
7
29
0
Order By: Relevance
“…In reality, S. hainanensis could maintain a rapid growth even when it was cultured at 35 • C. The transcriptomic results showed that, in addition to up-regulating genes involved in protein folding, oxidative stress, and ubiquitination processes, elevated temperature had a minimal effect on the transcription of genes involved in the basic metabolism of S. hainanensis, such as photosynthesis, carbohydrate metabolism, the cell cycle, and nutrient metabolism. As what previous studies have suggested for other organisms (Kumar et al, 2017;Ruocco et al, 2017), the up-regulation of genes related to protein folding (i.e., heat shock protein and chaperone) might contribute to the thermal acclimation of S. hainanensis. It is widely believed that the production of reactive oxygen species increases under elevated temperatures or other stresses, and plants/algae must activate their antioxidant defense mechanisms to protect themselves from oxidative damage (Ledford and Niyogi, 2005;Lazaro et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In reality, S. hainanensis could maintain a rapid growth even when it was cultured at 35 • C. The transcriptomic results showed that, in addition to up-regulating genes involved in protein folding, oxidative stress, and ubiquitination processes, elevated temperature had a minimal effect on the transcription of genes involved in the basic metabolism of S. hainanensis, such as photosynthesis, carbohydrate metabolism, the cell cycle, and nutrient metabolism. As what previous studies have suggested for other organisms (Kumar et al, 2017;Ruocco et al, 2017), the up-regulation of genes related to protein folding (i.e., heat shock protein and chaperone) might contribute to the thermal acclimation of S. hainanensis. It is widely believed that the production of reactive oxygen species increases under elevated temperatures or other stresses, and plants/algae must activate their antioxidant defense mechanisms to protect themselves from oxidative damage (Ledford and Niyogi, 2005;Lazaro et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…For transcriptional profiles, the effects of individual acidification and warming conditions on the response of marine algae and terrestrial plant have been widely reported (Li et al, 2008;Kumar et al, 2017;Ruocco et al, 2017). To our knowledge, however, data on the effect of the combined treatment of elevated temperature and acidification (AH) on marine algae have not been reported, and we do not know the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…L. leucocephala plots also had the highest nitrogen, calcium and sodium contents due to its ability to fix nitrogen more rapid through decomposition and its greater N recovery when incorporated into the soil (Pandey et al 2006;Oyebamiji et al 2016;Awopegba et al 2017;Kumar et al 2017). E. cyclocarpum was observed to have the highest potassium and magnesium contents due Means followed by the same letter(s) within the same column and treatment are not significantly different at 5 % level of probability using DMRT OC: Organic Carbon; N: Nitrogen; P: Phosphorus; K: Potassium; Ca: Calcium; Mg: Magnesium; Na: Sodium Means followed by the same letter(s) within the same column and treatment are not significantly different at 5 % level of probability using DMRT.…”
Section: Discussionmentioning
confidence: 99%
“…to its ability to conserve soil moisture, increase soil organic matter, and improve soil properties and microbial activity thereby enhancing mineralization rate and release of nutrient into the soil (Kumar et al 2017;Awopegba et al 2017). Consequently, L. leucocephala and E. cyclocarpum supplied higher organic carbon, total nitrogen, potassium, calcium, magnesium, and sodium to the soil (Oladoye et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The whole genome of brown algae Ectocarpus siliculosus, which constitutes a biological model for studying physiological and ontogenetic processes (Charrier et al 2008), has already been sequenced (Cock et al 2010) and the genomic information obtained has allowed identifying the molecular basis of different metabolic pathways specific to this organism (Groisillier et al 2014). RNAseq on Ilumina sequencing platform has been done with several species of Phaeophyta (brown algae) such as Saccharina japonica (Deng et al 2012), Sargassum thunbergii (Liu et al 2014), Sargassum vulgare (Kumar et al 2017), Ectocarpus siliculosus (Roeder et al 2005, Ditammi et al 2009, Martins et al 2013, Saint-Marcoux et al 2015, Macrocystis pyrifera (Konotchick et al 2012) and Macrocystis integrifolia (Salavarría et al 2018), as well as Rodophytas such as Pyropia haitanensis (Wang et al 2015). Dittami et al (2009) studied the global transcriptome expression pattern of the brown alga Ectocarpus siliculosus during a short thermal acclimation at three different abiotic stress conditions; demonstrating that at least one of these stressors regulate almost 70% of the gene expression.…”
Section: Introductionmentioning
confidence: 99%